The assisted writing model and its impact towards the upper secondary school students - Said, Rozita Radhiah; Jusoh, Zuraini (Human Resource Management Academic Research Society, 2021)
Written communication conveys information that can be used as record material or official documents for various purposes. However, this skill is often considered as the most difficult skill to be mastered, particularly among the upper secondary school students who will sit for Sijil Pelajaran Malaysia (SPM) Paper 1, Section B for Malay language paper. Thus, this action research has been carried out which related to writing skill by using a model of ‘SILA FOCKes SINI’ on 35 students at a secondary school in Serdang. The findings of the study showed a direct impact on the mean for student achievement in the pre-test, which is 37.17, while the mean for student achievement on the post-test is 73.03. The mean difference between post-test and pre-test was 35.857, which indicates a positive increment. The correlation between pre-test and post-test was 0.690, and the correlation statistic was significant (p < 0.05). This positive correlation and a high coefficient (r = 0.690) showed that students who obtained high marks in the pre-test were more likely to get high marks in the post-test. Based on statistics, the t-test was significant (t = 11.670; df = 34; p <0.05). Meanwhile, for the indirect impact, it showed an improvement of 11 criteria analyzed according to an identified scoring rubric of Sijil Pelajaran Malaysia. Teaching using the E-Writing model of ‘SILA FOCKes SINI’ has resulted in the development of better achievement in essay scoring. As an implication, this model is suitable to use as a reference for students, and teaching guide for teachers or prospective teachers at the upper secondary school level because it helps students to write in a structured, continuous, meet the requirements of the title and the writing to be more meaningful.